The Polish Mother on the defensive? The transformation of the myth and its impact on the motherhood of Polish women - IMBIEROWICZ, AGNIESZKA (Journal of Education Culture and Society, 2020)
The subject of this presentation is the attempt to defi ne and to present the origins, socio-cultural content and the evolution of The Polish Mother myth, present in the polish national consciousness. The author tries to show how this myth was born, what functions it fulfi lled and what forms it took in the changing historical and social reality, from the moment of loss of independence, through a period of real socialism, until the present day. The impact of this myth in the lives of real women and their motherhood is taken into consideration. Then, the author comparing the results of the latest polish sociological rese-arches on the family and its transformation, and transformation of value systems together with theories about the specifi cs of life in the period of postmodernity, wonders whether it’s time to deconstruct the myth of The Polish Mother, because it does not fi t the conditions of today’s world, which is characterized, above all, by the apotheosis of individuality, self–realization and freedom, or perhaps in polish society there is still strong traditionalism in thinking about motherhood, and the myth of The Polish Mother is still alive?